1992
DOI: 10.1287/inte.22.2.92
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Research Papers (Or How to Get an Academic Committee to Agree on Something)

Abstract: The College of Commerce and Finance at Villanova University sponsors an annual research aw^ards program. Its objectives are to encourage and reward faculty research efforts. The process of selecting papers to win the award turned out to be far more complex than we initially expected. After many unsuccessful attempts at developing a manageable procedure, we used the analytic hierarchy process to structure the selection process. We have used this approach for the last three years without any serious problems. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 9 publications
0
31
0
1
Order By: Relevance
“…Saaty (1980) suggests that if the CI/RI is smaller than 0.10, the degree of consistency is satisfactory; if, however, the CI/RI is larger than 0.10, there are inconsistencies and the AHP method may not yield meaningful results. Liberatore et al (1992) suggested the structured approach of AHP could better capture the subjective judgments. Millet (1998) found that the process could enhance shared understanding of decisions, save time, and facilitate consensus.…”
Section: Weight and Scorementioning
confidence: 99%
“…Saaty (1980) suggests that if the CI/RI is smaller than 0.10, the degree of consistency is satisfactory; if, however, the CI/RI is larger than 0.10, there are inconsistencies and the AHP method may not yield meaningful results. Liberatore et al (1992) suggested the structured approach of AHP could better capture the subjective judgments. Millet (1998) found that the process could enhance shared understanding of decisions, save time, and facilitate consensus.…”
Section: Weight and Scorementioning
confidence: 99%
“…The FPP method is proposed in the literature to face the inconsistency problems inherent in the Analytic Hierarchy Process. Following Liberatore's work (Liberatore, 1987;Liberatore, Nydick, & Sanchez, 1992), we introduce a modified version of the FPP method by employing the rating scale used in the pre-qualification stage in order to overcome the explosion in the number of pairwise comparisons when the number of alternatives and/or the number of sub-criteria is large. Without loss of generality, our proposal utilizes a rating scale with five levels.…”
Section: Proposed Approach For Supplier Selectionmentioning
confidence: 99%
“…The use of a five-grade rating scale to map different evaluation standards for qualitative criteria and absolute values for quantitative criteria has been employed in various problems with success and can be found in various studies (Lee, Lee, & Kang, 2005;Liberatore, 1987;Liberatore et al, 1992;Singh, Murty, Gupta, & Dikshit, 2007;Tam & Rao Tummala, 2001), albeit in the context of the AHP method. An example is shown in Table 1 for one qualitative and one quantitative criterion.…”
Section: Supplier Pre-qualificationmentioning
confidence: 99%
See 2 more Smart Citations